2015
DOI: 10.1097/mib.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Effect of Infliximab Is Reflected in the Clot Lysis Profile of Patients with Inflammatory Bowel Disease

Abstract: This is the first prospective study demonstrating that the clot lysis profile differs between patients with IBD and healthy individuals. On infliximab induction treatment, this clot lysis profile normalizes in responders suggesting that infliximab treatment is advisable for patients with IBD with an activated hemostatic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…14,27,28 Our data support the notion that more aggressive control of inflammation in IBD by means of TNF-α inhibition may lead to reductions in coagulation and fibrinolysis, which ultimately could reduce the risk of VTE. The observed protective association between TNF-α inhibitor use and VTE was strongest for young patients, which suggests that when IBD is the predominant risk factor for VTE, aggressive inflammation control with TNF-α inhibitors may lead to clinically significant VTE risk reduction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…14,27,28 Our data support the notion that more aggressive control of inflammation in IBD by means of TNF-α inhibition may lead to reductions in coagulation and fibrinolysis, which ultimately could reduce the risk of VTE. The observed protective association between TNF-α inhibitor use and VTE was strongest for young patients, which suggests that when IBD is the predominant risk factor for VTE, aggressive inflammation control with TNF-α inhibitors may lead to clinically significant VTE risk reduction.…”
Section: Discussionsupporting
confidence: 75%
“…13,14 However, it is not known whether use of TNF-α inhibitors reduces major VTE events in patients with IBD to a greater extent than use of other (nonbiologic) immunomodulatory treatments.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that patients with IBD who respond to infliximab treatment show a normalization of their initially altered clot lysis profile. The thromboembolic event prevalence in the IBD population included in this study was 5%, but only one patient developed thromboembolic event during the study [3]. We here report the case of this latter patient, a 31-year-old female patient with IBD.…”
Section: Introductionmentioning
confidence: 68%
“…In the follow-up of the institutional review board-approved B322201213950/S53684 prospective study described in Bollen et al [3], a 31-year-old woman (diagnosed with IBD 9 years ago) developed a deep vein thrombosis. October 2010, the patient received a first infusion of infliximab in combination with azathioprine for uncontrolled disease, with a second infusion at week 2 and a third infusion at week 6 (November 2010).…”
Section: Casementioning
confidence: 98%
See 1 more Smart Citation